The study of the correlation between international ovarian tumour analysis classification, risk of malignancy index and clinicopathological findings of adnexal masses - Kelagade, Mahadev; Thakur, Ruchi N.; Deshmukh, Sonali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Adnexal masses of ovarian origin are of growing concern these days due to high fatality associated with ovarian malignancy because they are diagnosed at advanced stage due to vague symptoms and absence of recommended screening tests. The present study aimed to assess the prediction potential of IOTA classification and RMI to clinicopathological findings of adnexal masses and calculate the sensitivity and specificity of same. Methods: This was a prospective observational study carried out on 96 non pregnant women presenting with adnexal mass to gynaecology OPD of a tertiary care hospital from 2020 to 2022. They were evaluated preoperatively with complete history, examination, ultrasound, and tumor markers. IOTA score and RMI was calculated for all patients. Following surgery, histopathology results were compared with preoperative evaluation. Statistical Analysis was done. Results: Mucinous cyst adenoma was the most common benign ovarian tumour, serous cystadenocarcinoma being the most common malignant ovarian tumour. Patients with malignancy were older and mostly postmenopausal. IOTA was found better than RMI with higher sensitivity 98.5% and high PPV 98.5%. Similarly, IOTA had higher specificity 91.7% and higher NPV 91.7% for identifying and prediction of benign patients. Conclusions: IOTA guidelines to describe sonographic features of adnexal masses have shown a high sensitivity and specificity for prediction of malignancy in adnexal masses and is a more reliable diagnostic tool over RMI tool for differentiation between benign and malignant adnexal masses.